ANALISIS CREDIT RISK DENGAN MENGGUNAKAN KONSEP PORTOFOLIO PADA BANK MANDIRI DAN BANK INTERNASIONAL INDONESIA - , Merliana; , Prof. Dr. Jogiyanto HM., MBA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The banking industry as institutions that have been always confronted with various kinds of risk in their management. The main risk of banking is credit risk. In order to that, risk need to identified, measured and controlled. Diversification is also the key of the portfolio management in credit for banking. One of the methods in credit risk measurement with portfolio concept and diversification system is KMVâs Portfolio Manager Models. This study aims to analyze credit risk in several industry sectors, viewed from return and risk of each industry sectors and to create an optimal portfolio for Mandiri Bank and BII in 2007 until 2011. Distributing credit for ten major industry will generated varied return and risk of each sector industry. In order to obtaining five optimal industry for Mandiri and BII, we need to know the value of coefficient variation of each industry sectors. With the method of Modern Portfolio Models, five optimal industries for Mandiri are Social Services Sector, Electricity, Gas and Water Sector, Mining Sector, Agriculture, Hunting and Agricultural facilities Sector and Transportation, Warehousing and Telecommunication Sectors. While the others five optimal industries for BII are Electricity, Gas and Water Sector, Agriculture, Hunting and Agricultural Facilities Sector, Social Services Sector, Business Service Sector and Construction sectors.